1998
DOI: 10.1002/(sici)1097-0274(199804)33:4<374::aid-ajim7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Median mononeuropathy among active workers: Are there differences between symptomatic and asymptomatic workers?

Abstract: The objective was to determine whether symptomatic workers with an abnormal sensory nerve conduction study consistent with carpal tunnel syndrome differed, in terms of electrophysiologic measures, psychosocial, demographic, anthropometric, or ergonomic variables, from workers with an asymptomatic median mononeuropathy. This was a cross‐sectional study of active workers at six different work sites. Cases were defined as workers with electrodiagnostic findings of a median mononeuropathy in either hand, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 11 publications
1
17
1
3
Order By: Relevance
“…In a cross-sectional study of 93 symptomatic and 91 asymptomatic active workers with median mononeuropathy (20.5 ms difference between the median and ulnar evoked peak sensory latency, 25% of the entire study population), Werner et a1 (71) found significant postural differences between the 2 groups in univariate analyses, including finger and wrist nonneutral postures. Other statistically significant differences between the 2 groups were gender, triceps skinfold thickness, history of diabetes, job insecurity, average hand force, and repetition level.…”
Section: Repetitionmentioning
confidence: 97%
“…In a cross-sectional study of 93 symptomatic and 91 asymptomatic active workers with median mononeuropathy (20.5 ms difference between the median and ulnar evoked peak sensory latency, 25% of the entire study population), Werner et a1 (71) found significant postural differences between the 2 groups in univariate analyses, including finger and wrist nonneutral postures. Other statistically significant differences between the 2 groups were gender, triceps skinfold thickness, history of diabetes, job insecurity, average hand force, and repetition level.…”
Section: Repetitionmentioning
confidence: 97%
“…1 Carpal tunnel syndrome (CTS) is one of the most common and disabling WMSDs, 6 affecting up to 25% of active workers. 3 The first published literature regarding diseases of workers was by Bernardino Ramazzini in 1700. His work is extensively cited in a recent article by Franco,7 who states that Ramazzini recognised that workers are susceptible to certain illnesses, and also noted that poor posture, repetitive movements and muscular loads contributed to certain disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos mais modernos sobre a prevalência de STC em trabalhadores foram realizados por pesquisadores da Ann Harbor University, Michigan, EUA 8,17,18 . Os três artigos referem-se a um grupo de cerca de 800 trabalhadores de atividades representativas da economia moderna frequentemente associadas com STC, como fabricação de móveis, contêineres, autopeças, velas de automóvel e processamento de dados.…”
Section: Stc E Trabalho Stc E Trabalho Stc E Trabalho Stc E Trabalho unclassified
“…Werner et al 17 não encontraram relação entre MM-0,5 (a "lesão") com atividade, mas relato de sintomas foi mais frequente em atividades de repetição alta e posturas forçadas do punho.…”
Section: Stc E Trabalho Stc E Trabalho Stc E Trabalho Stc E Trabalho unclassified
See 1 more Smart Citation